Efektifitas Pembinaan Kemandirian Terhadap Narapidana Lansia - Syalsabila, Githadana Ayu; Subroto, Mitro (Jurnal Panorama Hukum, 2021)
The exercise of coaching inmates in return to return to a good and acceptable society is essential. Elderly prisoners are part of vulnerable groups that cannot be compared to other productive - age inmates. Government regulation number 31 explains that convicts must get coaching, one of which is that they build self-reliance. Elderly prisoners are obliged to get coaching and can be adapted to a proper self-reliance program. The purpose of the writing is to know how effective the cultivation of independence toward older inmates is. Writing has been studied using qualitative methods with descriptive writing and approaches to legislation. In reality, there is still much to be said about the same process in which the self-reliance process is applied to the elderly and other productive age inmates. The service rendered to elderly (elderly) inmates has also not been seen, such as physical and spiritual service.